National Test System Design of China (Shanghai) Pilot Free Trade Zone - Xiao, Lin.; SpringerLink (Online service) (Singapore : Springer Singapore(Imprint), 2016)
This book discusses the latest developments in the China Pilot Free- Trade Zone strategy. It puts forward and explains the idea that building the Shanghai Pilot Free-Trade Zone (SFTZ) is a national test, as it is a major strategic decision to help China cope with the new situation resulting from opening-up and the further implementation of the reform. Based on China's strategic demand in the era of globalization, this book takes into account the global structure of trade, investment and changes in standards, and studies the system of SFTZ. Moreover, based on the national strategy of building international-caliber free-trade zone, it compares the SFTZ with other established free-trade zones and free-port cities. It reveals the overall SFTZ framework and explains in detail aspects of the financial system, investment management, trade supervision, taxation, offshore trade and finance, government system reform, plus the linkage mechanism of building Shanghai as an international economy, finance, trade and shipping center.
Chapter 1. Institutional Framework of China (Shanghai) Pilot Free Trade Zone (hereinafter CSPFTZ) -- Chapter 2. International Benchmarking of CSPFTZ -- Chapter 3. International Comparison of Free Trade Zone Institution -- Chapter 4. Financial System of CSPFTZ -- Chapter 5. Foreign Investment and Corporate Regulation of CSPFTZ -- Chapter 6. Tax System and Policy of CSPFTZ -- Chapter 7. Offshore Function System of CSPFTZ -- Chapter 8. CSPFTZ and Government Reform -- Chapter 9. CSPFTZ and Headquarters Economy -- Chapter 10. CSPFTZ and "the Four Centers of Shanghai" -- Chapter 11. CSPFTZ One-year-operation Review -- Chapter 12. Strategic Planning of CSPFTZ -- Chapter 13. The Linkage of the Further Development of CSPFTZ and the "Four Centers" Initiative in 2020 -- Chapter 14. The Linkage between the Further Development of CSPFTZ and the Building of the Sci-tech Innovation Center -- Chapter 15. The New Pattern of Global Governance and China's Strategy of Free Trade Zone -- Appendix 1. Series of Knowledge Points on CSPFTZ -- Appendix 2. Article Excerpts from the Interview of Mainstream Media -- Appendix 3. Important Documents of CSPFTZ.
Keywords: Development economics; Public Finance; Public Economics